Analisa Efisiensi Penjejak Sinar Matahari Dengan Menggunakan Kontrol ATMEGA16 - Agus Supriyadi; Jamaaluddin Jamaaluddin (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
Solar cells known so far still have many shortcomings in terms of Mounting and positioning against the sun, so the performance of solar cells in Battery charging is not maximal. There fore additional tools are required As a support for the solar cell to work optimally, and the electric current Is generated larger. Sunlight tracking with LDR system as As the sensor to direct to the sunlight rays will be compared With a passive system. Atmega16 as motor control and auto carger, LDR As a recipient of sunlight, DC motor as a direction player Sunlight. Solar cell is used with a capacity of 20 WP.And auto carger system using microcontroller is more cost-efficient and installation. After the two systems will be compared first in order Know the difference how much power generated by solar system Cell using a tracker and a passive one. Data retrieval will be Implemented for one week with sytem tracker and one week with Passive system. With the results of data to be in can be analyzed system comparison And known how much efficiency. Expected with a solar tracker system Cell can increase battery charging faster than with Passive position.